Kemampuan Komunikasi Keterampilan Dasar Mengajar Calon Guru Profesional Pada Program PPG Prajabatan - Lukitawati, Lukki (Direktorat Pascasarjana Universitas PGRI Kanjuruhan Malang, 2023)
This study aims to determine the ability of communication in the basic skills of teaching professional teacher candidates through the PPG Prajabatan program in the field of social studies education at Semarang State University. The method used in this research is descriptive quantitative, data analysis is done by reducing data, presenting data, to draw conclusions. The research data shows the communication skills of PPG Prajabatan participants in the components of opening lessons, managing classes, and closing classes. In the ability to open the class still needs to be improved again because there are still participants who get a sufficient assessment. In the ability to manage the class from all indicators ranging from the ability to ask questions, listen with empathy, and respond to various individual needs, overcome inappropriate behavior, make variations in learning, provide constructive feedback most of them have received very good and good ratings. In the ability to close the class there are still seven participants who get good grades.